Inhibitory effect of fermented mentha piperita on muc5ac in lung epithelial cells - Jee, Hye Jin; Bormate, Katrina Joy; Lim, Ok; Jung, Yi Sook (Journal of the Korean Society of Food Science and Nutrition, 2021)
Airway mucus hypersecretion is an important clinical manifestation of asthma and can be elicited by a wide variety of endogenous and exogenous stimuli leading to airway constriction and worsening of the disease. Gene expression for MUC5AC, a principal component of mucin, is known to significantly increase in the epithelial cells of patients with asthma. Therefore, many studies have proposed that regulating the MUC5AC expression in airway epithelial cells could be a target candidate as therapy for asthma treatment. Mentha piperita, also known as peppermint, is a popular medicinal herb due to its various pharmacological uses, and polyphenolic components with strong antioxidant activity. Based on these studies, we investigated whether peppermint could improve airway function through its inhibitory effect on phorbol myristate acetate (PMA)-induced expression of MUC5AC in NCI-H292 cells, a human airway epithelial cell line. Peppermint leaves were sourced from Herb Island and fermented with Bacillus subtillis. The fermented extract of peppermint (FEP) significantly reduced PMA-induced MUC5AC mRNA expression and protein release. FEP also inhibited the phosphorylation of extracellular signal regulated kinases (ERK) and U0126 (ERK inhibitor) inhibited PMA-induced MUC5AC expression and secretion. FEP also inhibited reactive oxygen species (ROS) production, and Trolox, a ROS scavenging agent, inhibited PMA-induced MUC5AC mRNA expression and protein secretion through the inhibition of ERK activation. These results suggest that FEP can protect the respiratory tract from inflammatory damage by reducing mucus hypersecretion through the ERK signaling pathway and antioxidant activity.
Keywords: Antioxidant; ERK; Fermented extract of peppermint; Mentha piperita; MUC5AC